ABNORMAL UTERINE BLEEDING IN REPRODUCTIVE WOMEN: DIAGNOSIS, MANAGEMENT AND TREATMENT - Venugopalan, Santhosh Kumar; Pandian, Nithya Sermuga; M, Pavani; Rao T, Srinivasa; Y, Rajini; Sk, Khadeer; V, Ravichandiran (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Abnormal Uterine Bleeding (AUB) is a common cause for concern among reproductive women and their families, as well as a frequent cause of visits to the Emergency Department and/or health care provider. In the pilot study which was conducted in 50 patients, observed that majority of patients were admitted due to menorrhagia and most of them were peri-menopausal women. Fibroid uterus is the most common cause in the study population, other than cyst and adenomyosis. Among the 50 patients, 54% were managed with drugs, 32% with surgery & drugs and the remaining with surgery alone. Among the drugs used, tranexamicacid is an effective therapy for the management of aub. The adolescents were treated with oral progestins. Anemia which was assessed in 20% and was corrected with folic acid supplements, iron sucrose and blood transfusions if required. Hysterectomy was done in majority of patients with cyst and fibroid excisions. Key words: AUB, Menorrhagia, fibroid uterus, tranexamic acid, progestins, anemia, hysterectomy